2012
DOI: 10.1126/science.1221339
|View full text |Cite
|
Sign up to set email alerts
|

Climate Change and Violent Conflict

Abstract: Current debates over the relation between climate change and conflict originate in a lack of data, as well as the complexity of pathways connecting the two phenomena.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
150
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 273 publications
(164 citation statements)
references
References 25 publications
4
150
0
3
Order By: Relevance
“…The question whether or not climate-related factors have significantly contributed to recent armed-conflict outbreaks has been heavily disputed in the scientific literature (33)(34)(35)(36)(37)(38). Although a sequence of studies has suggested that a large number of outbreaks of armed conflicts in modern as well as premodern times have been associated with climatic variability (33,36,37,(39)(40)(41), the robustness of these findings and underlying mechanisms are controversially discussed (10,37,42,43).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The question whether or not climate-related factors have significantly contributed to recent armed-conflict outbreaks has been heavily disputed in the scientific literature (33)(34)(35)(36)(37)(38). Although a sequence of studies has suggested that a large number of outbreaks of armed conflicts in modern as well as premodern times have been associated with climatic variability (33,36,37,(39)(40)(41), the robustness of these findings and underlying mechanisms are controversially discussed (10,37,42,43).…”
Section: Discussionmentioning
confidence: 99%
“…A clear shortcoming of most studies investigating the relation between climate change and armed conflicts is that they focus solely on meteorological indices such as temperature or precipitation time series (9,(39)(40)(41)(42)46), thereby neglecting the crucial importance of vulnerability and exposure for the impacts of climate hazards (35,47). This might be one reason for the substantial disagreement on the matter in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…However, work by Buhaug (8, p. 16480) reports that the original findings by Burke et al "do not hold up to closer inspection." This disagreement is widely cited by the media, policymakers, and other researchers (9)(10)(11) as statistical evidence that climatic conditions might not influence modern human conflict in sub-Saharan Africa. The extremity and persistence of this disagreement has recently prompted Solow (12, p. 180) to "call for peace on climate and conflict [research]," suggesting that "such disagreements indicate that a deeper look behind the statistics is warranted.…”
mentioning
confidence: 99%
“…Review studies until 2013 concluded with that there are limited links between climate anomalies and collective violence [30][31][32][33][34]. A meta-study and accompanying literature reviews by Hsiang, Burke and Miguel found a substantial and significant link [35][36][37].…”
Section: The Climate-conflict Debate Pre-2014mentioning
confidence: 99%